PENGARUH KONSENTRASI RAGI DAN WAKTU FERMENTASI PADA PEMBUATAN BIOETANOL DARI BIJI CEMPEDAK (Artocarpus champeden spreng) - Irvan, Ayu Wandira Putri, Sri Ulina Surbakti, Bambang Trisakti (Jurnal Teknik Kimia USU, 2016)
Needs fuel as a source of energy every day is increasing, while the energy reserves of petroleum (fossil) dwindling, therefore, to meet the needs of the fuel it is necessary to develop alternative fuels that are renewable and home environment (renewable ). Etonal Bioethanol is made from plants containing starch, sugar and other plant cellulose. Where in this study using jackfruit seeds that contain high enough carbohydrates as raw materials. This research aims to make bioethanol from cempedak seeds with various concentrations of yeast and fermentation time. The main process is hydrolysis; fermentation using yeast Saccharomyces Cereviciae; and purification by distillation and condensation. Variables used are changes in the concentration of yeast 3%, 6%, 9% and 2 days, 3 days, 4 days fermentation period. From the analysis of the research results obtained bioethanol yield per amount of raw materials is the best starting 12,5 ml/kg with a density of 0.962 g/ml and the calorific value sebasar 181.925 kcal/kg, which is the variation of the concentration of  9% and 3 days of fermentation period.